Augmentation of bladder using part of gaster during operation patient with sigmoid cancer (case report) - A. A. Voskresenskiy; N. V. Gerasimovskiy; N. M. Izumov (Koloproktologia, 2026)
A few papers on bladder augmentation in patient with local advanced colon cancer are found in literature. «Gold» standard here is small intestinal augmentation. A clinical case of using stomach for this is presented.